Manias, Panics and Crashes A History of Financial Crises - Kindleberger, Charles Poor 1910-2003; Aliber, Robert Z. 1930- (Palgrave Macmillan UK, 2001)
Manias, Panics and Crashes was first published in 1978, and dealt with financial crises that were, for the most part, before World War II. Black Monday of October 1987, along with more research especially on the years from 1880 to 1893 indicated a need for a second look. The third edition had its stimulus in the Japanese crash of January 1990, the effects of which carried through to decade. This new fourth edition covers the striking troubles of Mexico in 1994-95 and East Asia in 1997-98